Alien Gene Transfer in Crop Plants, Volume 2 Achievements and Impacts - Pratap, Aditya; Kumar, Jitendra (Springer New York : Imprint: Springer, 2014)
Alien gene transfer in crop plants from wild and genetically distinct resources enables engineered breeding to impart resistance to diseases and pests, tolerance to temperature extremities, problem soils and reduced water availability, as well as to improve yield, nutrition and storage. Encouraged by the success of alien gene transfer in crop plants, researchers have devised strategies to bring in useful genes even from across genome boundaries. Consequently, hundreds of genes of interest have been transferred in different crop species, thereby widening their genetic base and improving genetic potential. However, the success in improving crop plants through alien introgressions has remained variable in different crop species. While some crops have benefited tremendously from this  approach, others are less successful. This book provides a comprehensive reference on the practical aspects of alien introgressions in agricultural crops. Chapters written by eminent scientists from different countries around the world describe achievements and impacts of alien gene transfer in most important cereals, pulses, oil crops, vegetables and sugarcane.